Industrial Development in Nepal: Problems and Prospects - Khatri, Mukti Bahadur (Economic Journal of Nepal, 2018)
Industry has historically played an important role in contributing to economic growth and employment of many countries around the world. It is imperative to give high priority to Nepalese labor, skill and raw material based domestic investments to promote national level industries for achieving high employment and economic growth. So, this study examines analytically the industrial development of Nepal for the period 1960 to 2018 based on secondary data. As an outcome of this sector is found to be a more potential sector and contributing a significant role in sustain and wide economic growth in Nepal even in reality it has less contribution as its potential capacity in the past.